Negative brand meaning co-creation in social media brand communities: A laddering approach using NVivo - George Rossolatos (Psychology & Marketing, 2019)
Social media brand communities (SMBCs) have been heralded for their co-creative, participatory potential whereby consumers actively contribute to the proliferation of meaningful brand avenues in a virtuously circular relationship with brands. Elevated loyalty and enhanced brand equity have been posited repeatedly as likely outcomes of a positively engaged community of brand aficionados. However, evidence to the contrary as negative brand co-creation or brand co-destruction has been progressively piling up in the extant literature. This paper contributes to the meaning co-creation in SMBCs literature primarily on two grounds: first, by offering a methodological framework for adapting the laddering research technique in a mixed methods vein to SMBCs data in a thread-specific context, by leveraging the analytical capabilities of NVivo CAQDAS software; second, by addressing bottlenecks in the applicability of the proposed methodology in light of negative brand co-creation.
Keywords: 650; brand communities; brand meaning co-creation; laddering technique; NVivo; social media